iReenCAM: automated imaging system for kinetic analysis of photosynthetic pigment biosynthesis at high spatiotemporal resolution during early deetiolation - Veronika Balakhonova; Veronika Balakhonova; Tereza Dobisova; Tereza Dobisova; Zuzana Benedikty; Klara Panzarova; Jaromir Pytela; Radka Koci; Ioannis Spyroglou; Ingrid Kovacova; Dominique Arnaud; Jan Skalak; et al. (Frontiers in Plant Science, 2023)
Seedling de-etiolation is one of the key stages of the plant life cycle, characterized by a strong rearrangement of the plant development and metabolism. The conversion of dark accumulated protochlorophyllide to chlorophyll in etioplasts of de-etiolating plants is taking place in order of ns to µs after seedlings illumination, leading to detectable increase of chlorophyll levels in order of minutes after de-etiolation initiation. The highly complex chlorophyll biosynthesis integrates number of regulatory events including light and hormonal signaling, thus making de-etiolation an ideal model to study the underlying molecular mechanisms. Here we introduce the iReenCAM, a novel tool designed for non-invasive fluorescence-based quantitation of early stages of chlorophyll biosynthesis during de-etiolation with high spatial and temporal resolution. iReenCAM comprises customized HW configuration and optimized SW packages, allowing synchronized automated measurement and analysis of the acquired fluorescence image data. Using the system and carefully optimized protocol, we show tight correlation between the iReenCAM monitored fluorescence and HPLC measured chlorophyll accumulation during first 4h of seedling de-etiolation in wild type Arabidopsis and mutants with disturbed chlorophyll biosynthesis. Using the approach, we demonstrate negative effect of exogenously applied cytokinins and ethylene on chlorophyll biosynthesis during early de-etiolation. Accordingly, we identify type-B response regulators, the cytokinin-responsive transcriptional activators ARR1 and ARR12 as negative regulators of early chlorophyll biosynthesis, while contrasting response was observed in case of EIN2 and EIN3, the components of canonical ethylene signaling cascade. Knowing that, we propose the use of iReenCAM as a new phenotyping tool, suitable for quantitative and robust characterization of the highly dynamic response of seedling de-etiolation.